2007
DOI: 10.5694/j.1326-5377.2007.tb00857.x
|View full text |Cite
|
Sign up to set email alerts
|

The mental health and wellbeing of children and adolescents in home‐based foster care

Abstract: Objective: To identify the prevalence of mental health problems, rates of suicidal ideation and behaviour, and use of professional mental health services among children and adolescents residing in home-based foster care, and to compare these rates with those reported for children and adolescents in the general Australian community. Design: Cross-sectional survey. Participants and setting: 326 children and adolescents (aged 6-17 years) residing in home-based foster care in the Adelaide metropolitan region betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 14 publications
3
75
0
2
Order By: Relevance
“…Nevertheless, their scores were significantly higher compared with normative data. Comparable results were found by Mount et al 6 and Sawyer et al ,34 where carers (residential or foster carers) were four and two times respectively more likely to identify mental health needs than young people did themselves. These findings underline the necessity of using a multi-informant approach, both in epidemiological studies as in clinical practise.…”
Section: Discussionmentioning
confidence: 48%
“…Nevertheless, their scores were significantly higher compared with normative data. Comparable results were found by Mount et al 6 and Sawyer et al ,34 where carers (residential or foster carers) were four and two times respectively more likely to identify mental health needs than young people did themselves. These findings underline the necessity of using a multi-informant approach, both in epidemiological studies as in clinical practise.…”
Section: Discussionmentioning
confidence: 48%
“…Much research examining individuals with a history of FC has been performed during childhood and has shown that children with FC experiences exhibit heightened anxiety and associated internalizing problems (Damnjanovic, Lakic, Stevanovic, & Jovanovic, 2011; Dozier et al, 2002; Fisher, Gunnar, Dozier, Bruce, & Pears, 2006; Sawyer, Carbone, Searle, & Robinson, 2007; Wiik et al, 2011). Additionally, individuals with a history of caregiving adversity tend to be more stress reactive (McLaughlin et al, 2010) and exhibit altered activity of the stress-responsive hypothalamic pituitary adrenal (HPA) axis (e.g., flattened slope for cortisol production throughout the day and/or low cortisol morning levels) (Bernard, Butzin-Dozier, Rittenhouse, & Dozier, 2010; Bruce, Fisher, Pears, & Levine, 2009; Dozier et al, 2006; Fisher, Gunnar, Chamberlain, & Reid, 2000; Fisher et al, 2006; Fisher, Stoolmiller, Gunnar, & Burraston, 2007; Fisher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, children and youth in foster care often come to placements with complex behavioral and mental health needs, multifaceted placement histories, developmental and cognitive delays, insecure attachments, and chronic health problems (Brown, Arnault, George, & Sintzel, 2009; Chamberlain et al, 2008; Clausen, Landsverk, Ganger, Chadwick, & Litrownik, 1998; Coakley, Cuddeback, Buehler, & Cox, 2007; DeGarmo, Chamberlain, Leve, & Price, 2009; Egeland & Sroufe, 1981; Minnis, Everett, Pelosi, Dunn, & Knapp, 2006; Rauktis, Vides de Andrade, Doucette, McDonough, & Reinhart, 2005; Sawyer, Carbone, Searle, & Robinson, 2007; Shin, 2005; Whenan et al, 2009). Although Berrick and Skivenes (2012) described how the demands of foster caregiving often extend beyond those of “typical” parenting, research has found that foster caregivers may not be getting the training and support they need to meet the multidimensional needs of youth in their care (Dorsey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%